Bankruptcy and the Future of Aggregate Litigation: The Past as Prologue? - Troy A. McKenzie (Washington University Law Review, 2013)
Part I of this Article recounts the development of the law of business reorganizations and the sustained attack on bankruptcy practice that culminated in the hobbling of the reorganization bar during the New Deal. I provide a good deal of detail about these historical developments, because they are largely unknown to those in the complex litigation field. Understanding the path of business reorganization law helps to situate the later lessons I draw from the parallels between bankruptcy and the class action. Part II recounts the movement to reform and revive bankruptcy practice, a movement that helped produce a new Bankruptcy Code in 1978. The Code reversed key policy decisions made in the New Deal era and, as a consequence, spurred a revival of corporate reorganizations in the late twentieth century. Part III draws from that background and attempts to sketch out briefly—more in the form of questions than definitive answers—possible routes for the future development of aggregate litigation.
Keywords: bankruptcy; business reorganization; Receivership; New Deal; class action; Bankruptcy Code; aggregate litigation